2023
DOI: 10.3390/tropicalmed8030171
|View full text |Cite
|
Sign up to set email alerts
|

Zika, Flavivirus and Malaria Antibody Cocirculation in Nigeria

Abstract: Introduction. Arboviruses and malaria pose a growing threat to public health, affecting not only the general population but also immunocompromised individuals and pregnant women. Individuals in vulnerable groups are at a higher risk of severe complications from the co-circulation and transmission of ZIKV, malaria, and FLAVI fever. In sub-Saharan countries, such as Nigeria, these mosquito-borne infections have clinical presentations that overlap with other diseases (dengue, West Nile virus, and Japanese encepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Seroprevalence studies were conducted in 49 countries and territories, with a total of 63,864 individuals involved. These studies comprised 18 countries in Africa (including Burkina Faso [ 8 ], Cape Verde [ 9 ], Cameroon [ 10 ], Democratic Republic of the Congo [ 11 ], Ethiopia [ 12 ], Gabon [ 13 ], Ghana [ 14 ], Kenya [ 15 , 16 ], Madagascar [ 17 ], Mali [ 18 , 19 ], Nigeria [ 20 24 ], Republic of the Congo [ 25 ], Rwanda [ 26 ], Senegal [ 18 ], Sudan [ 27 ], Tanzania [ 28 ], The Gambia [ 18 ], and Zambia [ 29 , 30 ]); 13 countries in the Americas (Bolivia [ 1 ], Brazil, Colombia, French Guiana (see references in S2 Table ), Guatemala [ 31 ], Honduras [ 32 ], Jamaica [ 33 ], Martinique [ 34 ], Mexico [ 32 , 35 ], Nicaragua (references in S2 Table ), Peru [ 36 ], Puerto Rico [ 32 ], and Suriname [ 37 ]); 3 countries in the Eastern Mediterranean (Iran [ 38 ], Iraq [ 39 ], Saudi Arabia [ 40 ]); 3 countries in Europe (Cyprus [ 41 ], France [ 42 ] and Sweden [ 26 ]); 2 countries in Southeast Asia (Indonesia, Thailand (references in S2 Table ); and 10 countries in the Western Pacific region (China [ 43 45 ], Fiji […”
Section: Resultsmentioning
confidence: 99%
“…Seroprevalence studies were conducted in 49 countries and territories, with a total of 63,864 individuals involved. These studies comprised 18 countries in Africa (including Burkina Faso [ 8 ], Cape Verde [ 9 ], Cameroon [ 10 ], Democratic Republic of the Congo [ 11 ], Ethiopia [ 12 ], Gabon [ 13 ], Ghana [ 14 ], Kenya [ 15 , 16 ], Madagascar [ 17 ], Mali [ 18 , 19 ], Nigeria [ 20 24 ], Republic of the Congo [ 25 ], Rwanda [ 26 ], Senegal [ 18 ], Sudan [ 27 ], Tanzania [ 28 ], The Gambia [ 18 ], and Zambia [ 29 , 30 ]); 13 countries in the Americas (Bolivia [ 1 ], Brazil, Colombia, French Guiana (see references in S2 Table ), Guatemala [ 31 ], Honduras [ 32 ], Jamaica [ 33 ], Martinique [ 34 ], Mexico [ 32 , 35 ], Nicaragua (references in S2 Table ), Peru [ 36 ], Puerto Rico [ 32 ], and Suriname [ 37 ]); 3 countries in the Eastern Mediterranean (Iran [ 38 ], Iraq [ 39 ], Saudi Arabia [ 40 ]); 3 countries in Europe (Cyprus [ 41 ], France [ 42 ] and Sweden [ 26 ]); 2 countries in Southeast Asia (Indonesia, Thailand (references in S2 Table ); and 10 countries in the Western Pacific region (China [ 43 45 ], Fiji […”
Section: Resultsmentioning
confidence: 99%
“…Despite a modest decrease in malaria prevalence in recent years, as indicated by past research, many individuals globally, particularly in Africa, continue to grapple with malaria due to insufficient socio-economic status and access to treatment resources. (Das et al 2023 ; Mac et al 2023 ; Sarfo et al 2023 ; Taiwo et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [40] conducted a clinical and sero-epidemiological studies to help understand the hidden endemicity and disease burden of zika virus, malaria and other arbovirus in humans. There study showed an increase in hidden endemicity, antibody seropositivity as well as the possibility of zika virus, malaria and other flavivirus co-circulating in Nigeria.…”
Section: Introductionmentioning
confidence: 99%